PENDAMPINGAN GURU TERHADAP PEMBENTUKAN KARAKTER MORAL ANAK USIA DINI - Ridwan; Gunawan Putra, Eko (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Teacher mentoring plays a crucial role in the formation of moral character in early childhood, considering that this period is the golden age of child personality development. This study aims to describe the forms of teacher mentoring and its influence on the formation of moral character in early childhood. The method used was a qualitative approach, with data collection techniques through observation, interviews, and documentation. The research subjects included teachers and young children in Early Childhood Education (PAUD) institutions. The results show that teacher mentoring is carried out through various strategies, such as providing role models, fostering positive behaviors, effective communication, and reinforcing moral values ​​through play and enjoyable learning activities. Teachers act as facilitators, motivators, and behavioral models for children. Consistent and ongoing mentoring has been shown to be effective in shaping children's moral character, such as honesty, discipline, responsibility, empathy, and politeness. In conclusion, optimal and systematically planned teacher mentoring is highly influential in shaping the moral character of early childhood. Therefore, good pedagogical competence and teacher personality are required for the mentoring process to be effective and have a positive impact on children's moral development.